Uma abordagem para o problema de carregamento de navios-contêineres através do emprego de metaheurísticas baseadas na codificação por regras - Carraro, Luziana Ferronatto (Universidade do Vale do Rio dos Sinos, 2013)
With the expansion of maritime transportation, the use of containers for goods transportation has increased, being evidenced some problems. Among these problems, the container ship stowage problem arose as one of the main problems due to the high operational costs related to movement of containers. This problem is the focus of this research, where the main objective is the formulation of stowage plans that generate a minimum number of container shiftings in the operations of loading and unloading performed in port calls of container ships. In order to determine a suitable stowage plan, the application of Genetic Algorithm and Bee Swarm Optimization metaheuristics are proposed to solve the problem by using a rule-based encoding for the solution. The solution encoding based on loading and unloading rules is compact and suitable, ensuring the feasibility of solutions and also the simple representation of it, speeding up the solution procedures. In the performed experiments, both metaheuristics were applied assuming different rules settings with the objective to compare each performance. The proposal of new rules of loading and unloading, in addition with those existing in literature, has produced good solutions. Thereby, good quality solutions were achieved and also better than that found in the literature which discuss the same problem
Keywords: Carregamento de navios-contêineres; Algoritmo genético; Enxame de abelhas; Otimização combinatória; Container ship stowage; Genetic algorithms; Bees swarm; Combinatorial optimization; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação